The combination of vaccines and adjuvants to prevent the occurrence of high incidence of infectious diseases in bovine - Yao, Yiyang; Zhang, Zhipeng; Yang, Zhangping (Frontiers in Veterinary Science, 2023)
As the global population grows, the demand for beef and dairy products is also increasing. The cattle industry is facing tremendous pressures and challenges. The expanding cattle industry has led to an increased risk of disease in cattle. These diseases not only cause economic losses but also pose threats to public health and safety. Hence, ensuring the health of cattle is crucial. Vaccination is one of the most economical and effective methods of preventing bovine infectious diseases. However, there are fewer comprehensive reviews of bovine vaccines available. In addition, the variable nature of bovine infectious diseases will result in weakened or even ineffective immune protection from existing vaccines. This shows that it is crucial to improve overall awareness of bovine vaccines. Adjuvants, which are crucial constituents of vaccines, have a significant role in enhancing vaccine response. This review aims to present the latest advances in bovine vaccines mainly including types of bovine vaccines, current status of development of commonly used vaccines, and vaccine adjuvants. In addition, this review highlights the main challenges and outstanding problems of bovine vaccines and adjuvants in the field of research and applications. This review provides a theoretical and practical basis for the eradication of global bovine infectious diseases.Despite the remarkable results of VLP vaccines in the development of vaccines against bovine infectious diseases, it is worth noting that, at present, VLP vaccine research is mainly confined to small